2019
DOI: 10.1177/1178633719883282
|View full text |Cite
|
Sign up to set email alerts
|

Resurgence of Syphilis in the United States: An Assessment of Contributing Factors

Abstract: In the last decade, there has been a marked resurgence of syphilis in the United States despite the availability of effective treatments and previously reliable prevention strategies. The majority of cases are among the population of men who have sex with men (MSM); however, there has also been a recent increase among premenopausal women, coinciding with a concerning rise of congenital cases. The resurgence of syphilis can be largely attributed to changing social and behavioral factors, especially among young … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
136
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(141 citation statements)
references
References 69 publications
2
136
0
3
Order By: Relevance
“…Although several epidemiological studies have indicated anal sex as a risk factor for acquisition and transmission of T. pallidum among men who have sex with men [25][26][27], low evidence is found among heterosexual couples [22]. Indeed, this is one of the first investigations to report an association of anal sex between men and women and syphilis infection.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Although several epidemiological studies have indicated anal sex as a risk factor for acquisition and transmission of T. pallidum among men who have sex with men [25][26][27], low evidence is found among heterosexual couples [22]. Indeed, this is one of the first investigations to report an association of anal sex between men and women and syphilis infection.…”
Section: Discussionmentioning
confidence: 75%
“…Having anal sex with high frequency (> 50% of sexual encounters) during the last year was another factor that increased the prevalence of syphilis infection. Anal intercourse increases the risk of STIs because of the characteristic of the rectum, which shows a delicate tissue that can be easily damaged, which is aggravated by the limited lubrification, giving access to bacteria and virus to the bloodstream [22][23][24]. Studies have shown that anal intercourse carries one of the highest-risk of sexual activity for getting HIV.…”
Section: Discussionmentioning
confidence: 99%
“…The lesions of this pathological condition contain an abundance of lymphocytes, which makes the infiltration of HIV more recurrent. Furthermore, the immunosuppression caused by HIV may favor the evasion of the host defense mechanisms by T. pallidum 16,17 . A positive status for T. pallidum in patients with a previous history of STI may be associated with unprotected sex.…”
Section: Discussionmentioning
confidence: 99%
“…T. pallidum transmission rate was estimated to be 20% to 30% higher per sexual act. Besides, multiple partners increase the likelihood of transmission and dissemination of this pathogen 17 . It is important to note that condoms are not as effective to prevent infections that are transmitted through lesions, if it does not cover the wound 18 .…”
Section: Discussionmentioning
confidence: 99%
“…There has been an increase of 72% in the number of reported primary and secondary cases in the United States from 2013 to 2017, with the number of congenital syphilis cases increasing more than 150% from 2013 to 2018 [22][23][24]. It is thought that the increase in methamphetamine use, having sex with a person who injects drugs, injection drug use and heroin use are the primary factors that are leading to this dramatic increase in syphilis cases [22,25]. Acquired syphilis is typically divided into three stages: primary, secondary and latent.…”
Section: Syphilismentioning
confidence: 99%